Extreme‐Angle Silicon Infrared Optics Enabled by Streamlined Surfaces. Issue 11 (10th February 2021) - Zhang, Fei; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Guo, Yinghui; Gao, Ping; Yu, Honglin; Gu, Min; Luo, Xiangang
Abstract: Infrared optical systems are indispensable in almost all domains of society, but their performances are often restricted by bulky size, small field of view, large thermal sensitivity, high fabrication cost, etc. Here, based on the concept of catenary optics, a novel isophase streamline optimization approach is leveraged to design silicon complementary metal–oxide–semiconductor (CMOS)‐compatible metasurfaces with broadband, wide‐angle, and high‐efficiency performances, which breaks through the glass ceiling of traditional optical technologies. By using the truly local geometric phase, a maximum diffraction efficiency approaching 100% is obtained in ultrawide spectral and angular ranges. Somewhat surprising results are shown in that wide‐angle diffraction‐limited imaging and laser beam steering can be realized with a record field of view up to 178°. This methodology is scalable to the entire optical band and other materials, enabling unprecedented compact infrared systems for surveillance, unmanned vehicles, medical science, etc. Abstract : Ultralarge field of view (178°) diffraction‐limited imaging is experimentally realized using only a single‐chip planar element composed of silicon streamlined structures, with diffraction efficiency approaching 100% even at glancing incidence. These results are attributed to the isophase streamline optimization strategy for constructing streamlined structures with the ability of perfect wavefront generation and beyond the limit of insufficient phase sampling.